Poly(3-hexylthiophene) (P3HT)/Graphene nanocomposite material based organic field effect transistor with enhanced mobility - Tiwari S.; Singh A.K.; Prakash R. (My University, 2025)
The major drawback of organic field effect transistors (OFETs) is its lower mobility, which restricts their applications for high performance devices. Recently, graphene exhibits excellent carrier mobility, therefore, is used as a novel electronic substance for the fundamental research and several potential applications. Pristine graphene is not applicable in field effect transistors (FETs) for satisfactory on/off current ratio as it has no forbidden energy gap. Here, we report the fabrication as well as characterizations of poly-3-hexylthiophene (P3HT)/graphene nanocomposite (with two distinct concentrations i.e., 0.05 and 0.1 mg/ml of graphene in P3HT solution) based FETs to over come the limitations. The current-voltage (I-V) characteristics of P3HT/graphene based FETs are measured and key performance parameters of device are compared against only polymer P3HT based FETs. The analysis demonstrates that, in P3HT/graphene transistors some crucial parameters such as drain saturation current and mobility enhanced drastically although the on/off ratio reduced significantly. Our study demonstrates that presence of graphene in organic semiconductor and a synergic effect due to uniform distribution in the nanospace is an ordinary route to achieve high mobility OFETs which impart an affordable way for raising the performance of organic transistors. Copyright © 2014 American Scientific Publishers.